Literature in society - Rudaitytė, Regina (Cambridge Scholars Pub., 2012)
The essays in this volume focus on the text-world dichotomy that has been a pivotal problem since Plato, implicating notions of mimesis and representation and raising a series of debatable issues. Do literary texts relate only to the fictional world and not to the real one? Do they not only describe but also perform and thus create and transform reality? Is literature a mere reflection/expression of society, a field and a tool of political manipulations, a playground to exercise ideological a ...